(untitled) (Revista Electrónica Diálogos Educativos. REDE, 2017)
Oncological diseases have adverse connotations in people who suffer from them and in their family circle. This situation generates a large number of emotional reactions in them. The condition is associated with suffering and even death. This study aims to transform the scene of negative emotions that arise from the context of the hematoncologic patients and family. Thus from the voices of the social actors, were unveiled the actions to change the context lived in the everyday life of the disease. This study is part of the qualitative approach and sociocritical paradigm; which is based onto-epistemological and methodologically in the critical theory, characterized by dialectic interaction, Dialogic, and reflexivity. The method used was action research, information-gathering techniques: focus groups and in-depth interviews, as instruments were used the field notebooks, recorders and cameras. The information processing was carried out through the techniques of coding and categorizing. We also provide triangulation to ensure the credibility of the research. During the study, units of interpretation emerged: (a) the emotional journey against the disease, (b) a whole army after the light warriors, (c) family: the birthplace of rest and (d) a multicolored escape from a gray reality. All these exhibited emotional critical knots that patients have in the treatment of the disease process and allowed to design the plan of action that achieved the transformation of the emotionality of the patients.